Mala flavor preference increases risk of excessive gestational weight gain mediated by high-carbohydrate dietary patterns in Chongqing, China: an ambispective cohort study - Li, Jinghua; Wang, Difei; Mao, Yanyan; Zhang, Wuxia; Zhu, Qianxi; Liu, Jun; Du, Jing; Zhou, Weijin; Wang, Fen; Li, Min (Frontiers in Nutrition, 2025)
Taste preference drives food selection, acceptance, or rejection and influences nutritional status and body mass index. Nevertheless, there are few reports concerning pregnant women. Mala flavor, characterized by its “numbing” and “spicy” sensations, is a distinctive taste of Sichuan cuisine, created by the combination of Chinese prickly ash and chili peppers. We conducted a cohort study in Chongqing, China to analyze the impact of Mala flavor, on excessive gestational weight gain (GWG). The study included 495 pregnant women aged 20–45 years, without chronic diseases, who conceived naturally and had single pregnancies from May 2021 to November 2022. Demographic information and pregnancy outcomes were collected during the second trimester and post-delivery, respectively. Food intake and taste preferences, including fatty, salty, and Mala flavors, were assessed during the third trimester. Latent Profile Analysis revealed three dietary patterns: “high-carbohydrate diet” (HCD), “low-carbohydrate diet” (LND), and “moderate nutrient diet” (MND). Multiple logistic regression indicated that pregnant women preferring Mala flavor were more likely to follow an HCD and had a higher risk of excessive GWG. Moreover, those adhering to an HCD were at an increased risk of excessive GWG. Mediation analysis showed that the preference for Mala flavor influenced excessive GWG through HCDs, with a significant indirect effect and an insignificant direct effect. Our study suggests that a preference for Mala flavor is positively associated with excessive GWG, mediated by HCD patterns. However, these findings should be approached with caution due to the exploratory nature of the study.